2014
DOI: 10.1371/journal.pone.0104811
|View full text |Cite
|
Sign up to set email alerts
|

GlnR Negatively Regulates the Transcription of the Alanine Dehydrogenase Encoding Gene ald in Amycolatopsis mediterranei U32 under Nitrogen Limited Conditions via Specific Binding to Its Major Transcription Initiation Site

Abstract: Ammonium assimilation is catalyzed by two enzymatic pathways, i.e., glutamine synthetase/glutamate synthase (GS/GOGAT) and alanine dehydrogenase (AlaDH) in Amycolatopsis mediterranei U32. Under nitrogen-rich conditions, the AlaDH pathway is the major route for ammonium assimilation, while the GS/GOGAT pathway takes over when the extracellular nitrogen supply is limited. The global nitrogen regulator GlnR was previously characterized to activate the transcription of the GS encoding gene glnA in response to nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…In actinomycetes, GlnR was typically viewed as a global nitrogen metabolism regulator before, governing many nitrogen metabolism related processes (Fink et al, 2002;Tiffert et al, 2008;Wang and Zhao, 2009;Wang et al, 2012Wang et al, , 2013Wang et al, , 2014. Recently, several studies have reported that the GlnR homologs in Streptomyces regulate the biosynthesis of some antibiotics, e.g., actinorhodin, avermectin and validamycin (Qu et al, 2015;He et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In actinomycetes, GlnR was typically viewed as a global nitrogen metabolism regulator before, governing many nitrogen metabolism related processes (Fink et al, 2002;Tiffert et al, 2008;Wang and Zhao, 2009;Wang et al, 2012Wang et al, , 2013Wang et al, , 2014. Recently, several studies have reported that the GlnR homologs in Streptomyces regulate the biosynthesis of some antibiotics, e.g., actinorhodin, avermectin and validamycin (Qu et al, 2015;He et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In actinomycetes, GlnR is an OmpR-type transcriptional regulator, and those early studies show that most GlnR-regulated genes (e.g., amtB, nirB, nasA, ureA, glnA, and ald) are involved in the assimilation and utilization of a variety of nitrogen sources, such as ammonium, nitrate and urea (Fink et al, 2002;Tiffert et al, 2008;Wang and Zhao, 2009;Wang et al, 2012Wang et al, , 2013Wang et al, , 2014. Accordingly, the GlnR in actinomycetes is mainly considered as a global nitrogen metabolism regulator.…”
Section: Introductionmentioning
confidence: 99%
“…Production of His-tagged Amycolatopsis mediterranei GlnR (AME_GlnR) was the same as described before (31,33). For purification of Streptomyces avermitilis GlnR (SAV_GlnR), primers PglnRsav-fw and PglnRsav-rv were used to amplify the structure gene of S. avermitilis glnR, which was further cloned into the NdeI and EcoRI sites of pET28a, yielding the expression plasmid pET-glnRSav.…”
Section: Methodsmentioning
confidence: 99%
“…The ectoine and hydroxyectoine biosynthetic genes of ect-ABCD are present in most actinomycetes (25). As GlnR-mediated regulation of nitrogen metabolism is also very conserved in actinomycetes (29,31,33,35,36), it is thus hypothesized that GlnR regulates the expression of ect genes in actinomycetes that contain both GlnR and ect genes.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation